Melamine-formaldehyde resins modified with glycerol - L. Carvalho (2015)
Melamine-formaldehyde resins represent an important class of aminoplastic resin and are made by the reaction of formaldehyde with mainly melamine. Melamine-formaldehyde resins are used as adhesives for plywood and particleboard for use in humid and exterior conditions and are also used for the impregnation of paper sheets in the production of selfadhesive overlays for the surface of wood-based panel products and of self-adhesive laminates [1]. During the last decade the interest in using raw materials based on bio-renewable resources for synthetic polymers and composite materials increased largely [2]. Recent developments in eco-efficient bio-based adhesives for wood bonding include the use of tannins, lignin, proteins, and carbohydrate derived natural binders. The main goal of this work is the partial replacement of melamine in melamine-formaldehyde resins by glycerol, yielding a stable resin with potential for use in impregnated paper based laminates.